First mitochondrial genome of Lutjanus ehrenbergii_ Peters 1869 (Lutjaniformes: Lutjanidae: Lutjanus) and phylogenetic analysis - Zengliang Miao; Shiyi Chen; Tingting Wang; Xun Jin; Shufei Zhang; Sixu Zheng; Yunpeng Wang; Taobo Feng; Luxiu Gao; Jian Chen (Mitochondrial DNA. Part B. Resources)
The complete mitochondrial genome of the Lutjanus ehrenbergii was sequenced by Sanger platform. The circular mitogenome of L. ehrenbergii (16,512 bp) encoded the typical 37 genes, and one non-coding regions. All of the protein-encoding genes were located on the H chain except ND6. The nucleotide composition was A (28.04%), T (24.84%), C (30.89%) and G (16.23%). Phylogenetic analysis based on the 13PCGs sequences showed that L. ehrenbergii was closely related to the sister species of Lutjanus russellii and Lutjanus carponotatus. These studies provided important mitochondrial genome data of L. ehrenbergii, phylogenetic tree analysis revealed the position of L. ehrenbergii in Lutjaniformes.